2012
DOI: 10.1111/j.1365-2788.2011.01515.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactional patterns between staff and clients with borderline to mild intellectual disabilities

Abstract: The interactional patterns found in this study suggest that staff and clients can face difficulties establishing collaborative dialogues on shared topics. Future research should take account of what staff and clients want to achieve in dialogues, along with the nature of their non-verbal communication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…This supports literature that these qualities are not naturally present in all individuals (Culham ; Reuzel et al . ; Kellett ; Nind & Powell ; Healy & Walsh ). The Intensive Interaction course was highly useful within the workplace.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This supports literature that these qualities are not naturally present in all individuals (Culham ; Reuzel et al . ; Kellett ; Nind & Powell ; Healy & Walsh ). The Intensive Interaction course was highly useful within the workplace.…”
Section: Discussionmentioning
confidence: 99%
“…The literature provides substantial evidence to suggest behavioural elements such as patience, empathy and adapting communication style are not naturally present in all carers (Culham ; Reuzel et al . ; Kellett ; Nind & Powell ; Healy & Walsh ). More importantly, these behaviours may not be exercised consistently or confidently enough to produce or maintain the desired effect (Watson & Fisher ).…”
Section: Introductionmentioning
confidence: 99%
“…Perinbanayagam (2003) adds that greater involvement in the interaction and mutuality of parties leads to favorable judgments of credibility and attractiveness of messages that are exchanged. Another study by Reuzel et al (2013) revealed that individuals that are highly involved in an interaction, recall more factual information and argument content from conversations. They also present more logical arguments, process more information, are better at adjusting their behaviors in relation to the messages, and can easily accomplish conversational goals.…”
Section: Literature Review On the Relationship Between Variablesmentioning
confidence: 99%
“…Earlier research found that direct support staff were not always prepared sufficiently to provide skilful communication support for the wide range of individual needs they encountered in their work (see Bradshaw, 2001; McConkey et al , 1999). Not restricted to individuals with more complex needs, disparities in the communication process between staff and individuals with borderline-mild learning disabilities have been reported, affecting the synchrony of verbal and non-verbal aspects (Reuzel et al , 2013a) and the pattern of turn occupation by staff where direct questions dominated and there was neglect of some spontaneous contributions by service users (Reuzel et al , 2013b). Dalton and Sweeney (2013) reported that whilst support staff acknowledged the importance of good communicative support to the improved quality of life amongst people with learning disabilities, they also recognised their own lack of knowledge and poor availability of specific resources as problematic.…”
Section: Bi-directional Influencesmentioning
confidence: 99%